Evaluation of users' level of satisfaction for an artificial intelligence-based diagnostic program in pediatric rare genetic diseases. Issue 28 (15th July 2022) - Choi, In Hee; Seo, Go Hun; Park, JeongYun; Kim, Yoon-Myung; Cheon, Chong Kun; Kim, Yoo-Mi; Oh, Arum; Byeon, Jung Hye; Kang, Eungu; Shin, Young-Lim; Lee, Ji Eun; Kim, Su Jin; et al.
Abstract : The artificial intelligence (AI)-based genetic diagnostic program has been applied to genome sequencing to facilitate the diagnostic process. The objective of the current study was to evaluate the experience and level of satisfaction of participants using an AI-based diagnostic program for rare pediatric genetic diseases. The patients with neurodevelopmental disorders or hearing impairments, their guardians, and their physicians from 16 tertiary general hospitals were enrolled. The study period was from April 2020 to March 2021. A survey was designed to assess their experience and level of satisfaction. A total of 30 physicians and 243 patients and guardians (199 neurodevelopmental disorders and 44 hearing impairments) completed the survey. DNA samples of the subjects were collected through buccal swabs or blood collection: 211 subjects (86.8%) through buccal swab and 29 subjects (11.9%) through blood collection. Average turnaround time for result receipt was 57.54 ± 32.42 days. For the sampling method, 193 patients and guardians (81.1%) and 28 physicians (93.3%) preferred buccal swab. The level of satisfaction of the 2 groups participating in the AI-based diagnostic program was 8.31 ± 1.71 out of 10 in the patient and guardian group and 8.42 ± 1.23 in the physician group. Clinicians, patients, and guardians are satisfied with the AI-based diagnostic program in general. With an increase in AI-based precision medicine solutions, the evaluation of the user's satisfaction with appropriate provision will help improve personal health care.